Effect of the Dates Milkshake on the Duration of the First Stage of Labor - Wahyuni, Elly; Baska, Dwie Yunita (Althea Medical Journal, 2024)
Background: Prolonged labor can occur due to malnutrition during the first stage of labor. During the labor process, women need foods rich in sugar, such as dates milkshake, to optimize uterine contractions. This study aimed to explore the effect of dates milkshake on the duration of the first stage of labor.Method: This study was a quasi-experiment conducted from August to November 2021 in Bengkulu City, Indonesia using a posttest-only design with nonequivalent groups. Participants included 34 primigravida and multigravida women who were then divided into intervention group who received dates milkshake and control group who received local fruit juice, each with 17 participants. Daily routine consumption and the partographs during labor were observed. The data obtained was analyzed using Mann Whitney and Cochran’s and Mantel-Haenszel.Results: The duration of labor in mothers given dates milkshake averaged 4.1 hours (± 0.697), ranging from 3 to 5 hours; meanwhile the control group averaged 7 hours (± 1.904), ranging from 5 to 11 hours. There was a significant difference in the duration of labor between mothers given dates milkshake and local fruit juice (p= 0.000, OR=4.0).Conclusions: Dates milkshake has an effect on shortening the duration of the first stage of labor. Dates milkshake can be used as a viable food choice for pregnant women to help maintain and increase maternal energy availability during childbirth.